(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Telemedicine has become an integral part of health care, particularly in the institutions of tertiary care where the complexity of the conditions often calls for timely interventions. Telemedicine is the application of telecommunication technology in order to provide and promote access to healthcare, especially for remote or medically isolated populations Objective : The objective of the study was to assess the knowledge, attitude and practice regarding telemedicine among nurses at tertiary care hospital setting. Methods : It was a cross sectional, quantitative study, conducted at Sheikha Fatima Institute of Nursing and Allied Health Sciences Lahore. One hundred and eighty-six nurses of both genders were included in the study who anonymously filled questionnaire containing demographic details, professional details and response related to knowledge, attitude and practice regarding telemedicine. The data was entered and analyzed using the statistical package for social sciences version 22.0. Results: Knowledge, attitude and practice of 186 nurses regarding telemedicine was assessed and 127(68.2%) possess accurate knowledge about telemedicine and 59(31.7%) have poor knowledge and it is not ignorable figure. 41(22%) of the nurses shows negative attitude toward the telemedicine and 145(68.2%) shows positive attitude toward telemedicine. Regardless of accurate knowledge and positive attitude of nurses in majority, telemedicine practice is poor among nurses because of several factors. 108(58%) of the nurses participants have poor practice and 42% of nurses shows good practice association between job experience and knowledge of nurses related to telemedicine because the P value is 0.004 and there is no significant association with department of nurses and knowledge of telemedicine (P- 0.41). Conclusion Nurses working in tertiary care hospital reported good knowledge toward the telemedicine and thy completely understand the phenomenon of telemedicine. Nurses want to practice digital health services thus show positive attitude toward telemedicine However, some of the participant nurses considered digital health services or mobile nursing care through media an extra burden on nurses. Association of knowledge and job experienced analysis shows that as the length of service increases telemedicine knowledge increases. At the same time the practicing ratio was low due to lack of facilities and improper channel.